PENERAPAN IRIGASI HIDROPONIK SISTEM AKAR TELANJANG (Bare Root System) PADA TANAMAN KANGKUNG (Ipomea Aquatic forsk). - Tulung, Ronaldo; Rumambi, David P.; Ludong, Daniel P. M. (EUGENIA, 2019)
This study aimed to test the application of the Deep Flow Technique (DFT 4cm dan DFT 2cm)Â  and Nutrient Film Tecnique (NFT) bare root system hydroponic system on water spinach plants by calculating plan water requirements and measuring vegetative growth of water spinach plants with thickness / water level different. The results showed that the CU (Coefficient Uniformity) value was 95% in that DFT 4cm, 111,55ml of water as used, plant height and number of leaves were relatively that same as t6he other treatments with a plant mass weight of 181.28gr, with a stem meter of 12.92cm. DFT 2cm required 90.17ml of water with a plant mass weight of 160.33gr. NFT needs water as much as 106.57 ml with a plant mass weght of 153.28gr.